The amortization of vibrations on machines - case study - Latifi, Ahmet; Abazi, Arsim; Shartari, Astrit (International Journal of Engineering and Technology, 2017)
When determining the static rigidity of the machine, only loads of constant forces are taken into account. However, machine details are not loaded only with static forces but also with external and internal dynamic forces. Components of static forces affect the form errors, while dynamic instability, and as a result of dynamic forces have negative impact on: the severity of processed surface, the wear of the metal cut-ting tool, wear of the machine details and productivity.
Keywords: Vibration; Amortization; Isolation; Machine; Cutting Tool; Wear; Force.